Pest categorisation of Apiosporina morbosa - Jeger, Michael (John Wiley and Sons Inc., 2018)

(untitled) (EFSA J)
The Panel on Plant Health performed a pest categorisation of the fungus Apiosporina morbosa, the causal agent of black knot, for the EU. The identity of the pest is well established and reliable methods exist for its detection/identification. The pest is listed in Annex IIAI of Directive 2000/29/EC and is not known to occur in the EU. Apiosporina morbosa is present in Alaska, Canada, Mexico and the continental states of the USA. The major hosts of A. morbosa are Prunus domestica and Prunus cerasus; the host status of other Prunus species and hybrids is uncertain because of contradictory reports or lack of information. The pest could potentially enter the EU on host plants for planting and plant parts originating in infested third countries. Wood of Prunus spp. is also a pathway of entry, but of minor importance. The current pest distribution and climate matching suggest that the pest could establish and spread in the EU wherever the hosts are grown. In the infested areas, the pest causes girdling of twigs and occasionally of larger branches, whereas trees with multiple infections loose vigour, bloom poorly, and become unproductive, stunted and susceptible to winter injury and infection by other pathogens. The presence of black knots makes trees unsuitable for timber production. It is expected that the pest introduction and spread in the EU would impact host production. Uncertainty exists on whether the agricultural practices and chemical control methods applied in the EU could prevent the establishment and spread of A. morbosa. A. morbosa meets all the criteria assessed by EFSA for consideration as potential Union quarantine pest. As the pest is not known to occur in the EU, this criterion to consider it as Union regulated non‐quarantine pest is not met.